Effects of calcination temperatures on the structure–activity relationship of Ni–La/Al2O3 catalysts for syngas methanation. Issue 7 (27th January 2020) - Wu, Hongli; Zou, Meng; Guo, Lisheng; Ma, Fengyun; Mo, Wenlong; Yu, Yuming; Mian, Inamullah; Liu, Jingmei; Yin, Shuangjie; Tsubaki, Noritatsu
Abstract : Calcination temperature affects the existing types of NiO, and the influence of the three NiO types on the catalytic activity of samples is bound type ≫ free type > combined type. Abstract : A series of Ni–La/Al2 O3 catalysts for the syngas methanation reaction were prepared by a mechanochemical method and characterized by thermogravimetric analysis (TG-DTA), X-ray fluorescence (XRF), X-ray diffraction (XRD), N2 adsorption–desorption, H2 temperature-programmed reduction (H2 -TPR), and X-ray photoelectron spectroscopy (XPS). The calcination temperatures (350–700 °C) had significant impacts on the crystallite sizes and interactions between NiO and Al2 O3 . The catalyst calcined at 400 °C (cat-400) showed a 12.1% Ni dispersion degree and the maximum bound state of NiO (54%) through the Gaussian fitting of H2 -TPR. Cat-400 also achieved the highest CO conversion, CH4 selectivity and yield. Cat-400 exhibited good stability and catalytic activity in a lifetime testing of 200 h. The deactivation of cat-400 was mainly caused by carbon deposition according to the data from XRD, TG-DTG and XPS.